Dentosept application influence on outcome of surgical treatment of retained lower third molars - Szupiany, Teresa; Ciągło, Bartłomiej; Sanchez-Lugo, Jorge; Pytko-Polończyk, Jolanta (Journal of Stomatology, 2015)
Introduction. Surgical extraction of retained lower molars is one of the most difficult procedures on the alveolar ridge. It traumatizes the surrounding tissue, which may frequently lead to complications such as pain, swelling and lockjaw that pass after three to four days. Often, it may cause long-lasting and more burdensome complications. In order to avoid those complications, analgesics, antibiotics and topical antiseptics are used. Numerous scientific studies point to the need to find a pharmacological agent that would effectively support the effects of surgical treatment of retained lower teeth molars. Aim of the study. To evaluate the efficacy of Dentosept in treatment of pain and swelling after surgical extraction of third molars. Material and Methods. Medical product used in this study was Dentosept (Phytopharm). The study included twenty patients in whom surgical extraction of the lower right or left molar was planned, regardless of gender. Half of the patients were treated with Dentosept. The product was used in the form of a 15% aqueous solution directly before the surgical treatment (rinsing the mouth for one minute), immediately after the extraction procedure and suture (gauze pad soaked with Dentosept placed for twenty minutes), and several more days after tooth extraction (rinsing the mouth with 15% solution, twice daily for seven days). The remaining patients constituted the control group, for which no specific preparations before and after surgeries were recommended. Results. Dentosept demonstrated efficacy in the treatment of postoperative pain after third molars surgical extraction compared with the control group. Conclusions. Dentosept may be used as adjunctive therapy in the surgical treatment of lower third molars. The anti-inflammatory components, antibacterial and bacteriostatic properties support wound healing, affect and improve the subjective feeling of the patient after tooth extraction.